Light intensity distribution in multi-lamp photocatalytic reactors - Boyjoo, Yash; Ang, Ha Ming; Pareek, Vishnu (Pergamon, 2013)
A computational fluid dynamics approach has been used to investigate the effect of lamp separation (Xlamp) on the radiation intensity distribution in a multiple-lamp photocatalytic reactor. The optical parameters (absorption and scattering coefficients) of Aeroxide® P25 titanium dioxide (TiO2) were determined by performing experiments using a single lamp system. Since the optical properties are wavelength dependent, the range of wavelength from the UV lamp was divided into 4 bands, and optical properties in each of the bands were determined by matching the experimental observations with simulated values. Simulations were then carried on multiple-lamp (2 and 4 lamps) photoreactors as a function of lamp separation and catalyst loadings. In case of 2-lamp system, the maximum local volumetric rate of energy absorption (<LVREA>) occurred at Xlamp=40mm, and it was independent of the catalyst loading. With 4 lamps however, optimum Xlamp was dependent on the catalyst loading. At low loads (up to Wcat=0.06gL-1), the optimum Xlamp was 80mm but as the catalyst concentration increased, the value of the optimum lamp separation decreased considerably, with 30mm for Wcat=0.07gL-1 and decreasing further as the concentration further increased. Because of the high absorption coefficient of the catalyst, the wall emissivity had a negligible effect on the <LVREA> for both configurations, even when the lamps were close to the wall. Finally, in both cases, the optimum lamp separation was independent of the lamp emissive power.